Modelling ecological pressures and responses in a west of Ireland lake - Murnaghan, Sarah (Trinity College (Dublin, Ireland). Department of Geography, 2013)
Effective lake management requires an understanding of aquatic ecological pressure response relationships. Deciphering the aquatic effects of multiple ecological pressures, such as climate variability and human activity, requires the analysis of long terni monitoring data. However, monitoring data are rarely available, particularly for the period prior to human impact. Palaeolimnology can be used to investigate long term aquatic ecological pressures and responses, and the benefits of palaeolimnology for lake management have been well-established. Dynamic ecological modelling can also be used to reconstruct ecological pressures-responses relationships. However, although recognised as a potentially valuable tool for water quality management, ecological modelling is not widely applied in lake management.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin.